THE DECLINE OF MELAYU LANGUAGE IN PATANI - AU-SEN, MUHAMMADSURTAN
Malay has reached the glorious stage some time ago to be the lingua franca and the language of science. However, Patani Malay dialect started to change since the launch base Siamisasi Thai kingdom, namely Kempen improve the culture of the call Ratthaniyom Thai. The use of textbooks and exams will be determined by the Thai Ministry of Education, when all religious teachers let registered in line with ministry rules. Stakeholders are expected to get involved in this effort. Measures for restoring to make the language great and Patani Malay language needs to happen on a regular basis. Starting from parents which is a prelude to nurture and sow the seeds to childhood onwards by an educational system that fingering a role in this. Thus, let the new generation of heavy slump speak the mother tongue and love language of our ancestors so that the Malay language continued in use until the children and grandchildren and will reach the stage of a glorious future.